Investigation of hallmarks of carbonyl stress and formation of end products in feline chronic kidney disease as markers of uraemic toxins. Issue 6 (June 2019) - Valle, Emanuela; Prola, Liviana; Vergnano, Diana; Borghi, Roberta; Monacelli, Fiammetta; Traverso, Nicola; Bruni, Natascia; Bovero, Andrea; Schiavone, Achille; Nery, Joana; Bergero, Domenico; Odetti, Patrizio
Objectives: Cats are commonly affected by chronic kidney disease (CKD). Many reactive carbonyl intermediates and end products originating from the oxidative stress pathways are recognised as uraemic toxins and may play a role in CKD progression. The aim of the present study is to confirm whether carbonyl end-product formation is higher in cats affected by CKD and to assess whether an angiotensin-converting enzyme inhibitor (ACEi) might affect these hallmarks. Methods: Twenty-two cats were divided into three groups: a control group (CG), cats with CKD and cats with CKD treated with an ACEi. Serum levels of pentosidine, carboxymethyllysine, advanced oxidation protein products, malondialdehyde, methylglyoxal and hexanoyl-lysine were measured. In addition, biochemical parameters and systolic blood pressure were evaluated. After checking for normality, comparisons between groups were performed followed by multiple comparison tests. P values ⩽0.05 were considered significant. Correlations between concentrations of the considered biomarkers and of the other metabolic parameters were investigated. Results: Advanced oxidation protein products, malondialdehyde and hexanoyl-lysine concentrations were significantly higher in CKD and ACEi-treated groups compared with the CG ( P <0.05). Carboxymethyllysine increased in the ACEi-treated group when compared with the CG, whereas intermediate values of these biomarkers were found in the CKD group ( P <0.05). The ACEi-treated group showed the highest values of carboxymethyllysine, advanced oxidation protein products and hexanoyl-lysine. By contrast, the CKD group had the highest concentration of malondialdehyde. No statistically significant difference was found in the levels of pentosidine or methylglyoxal. End products correlated with creatinine and urea and with each other. Conclusions and relevance: Significantly high concentrations of both intermediate and end products of carbonyl/oxidative stress were detected in CKD cats. This is the first study to have concurrently taken into account several uraemic toxins and biochemical parameters in cats affected by CKD.